LITERACY STUDY: MILITARY VS CIVILIAN LEADERSHIP STYLES IN HOSPITAL MANAGEMENT IN INDONESIA - Audrianto; Kosasih (RADJA PUBLIKA, 2026)
Leadership is a strategic factor in determining the effectiveness of hospital management, particularly in addressing the complexities of the modern healthcare system. In the Indonesian context, military hospitals exhibit distinct leadership characteristics compared to civilian hospitals, namely leadership based on discipline, hierarchy, obedience to command, and mission orientation. This literature review aims to comprehensively analyze the implementation of a military leadership style in hospital management in Indonesia, including its advantages, limitations, and implications for organizational and healthcare worker performance. The method used is a systematic literature review with a narrative approach to various scientific publications from 2020–2026 obtained from reputable international journals, global health organization reports, and indexed national publications. The study results indicate that a military leadership style has advantages in organizational discipline, operational efficiency, cross-unit coordination, and crisis management, particularly in emergency situations such as the COVID-19 pandemic and health disaster management. However, this leadership style also has limitations, particularly in aspects of interpersonal communication, organizational flexibility, healthcare worker participation, and psychological safety. Recent literature indicates the need for a hybrid leadership model that integrates the strengths of military leadership with a more participatory and humanistic civilian leadership approach. This study also identifies several research gaps, including a lack of comparative empirical research in Indonesia, a lack of longitudinal studies, and limited exploration of the influence of organizational culture on the effectiveness of military leadership in hospitals. Theoretically, this study broadens our understanding of leadership adaptation across sectors, while practically providing implications for developing more adaptive, effective, and contextual hospital leadership models within the Indonesian healthcare system.